Literasi Zakat: Interpretasi Masyarakat Terhadap Kewajiban Membayar Zakat - Uswatun Hasanah; Muhammad Maghfur; Moh. Nurul Qomar (Journal of Islamic Social Finance Management, 2021)
Nationally the gap of zakat potential with the reality of zakat really happens, one problem is low zakat literacy. This research seeks to examine the level of zakat literacy in the community's scope, namely in Dukuh Krajan Mayonglor Village Jepara Regency. Focus on this research is the level of understanding of society towards the obligation to pay zakat. In this study used a qualitative method, is a data got by reviewing and efforts to explore phenomena in society as an aim data source in the field. Researchers use interviews,    observations and documentation in data collection techniques.   The results showed  that the community of  Dukuh Krajan  understands the basic knowledge of zakat  well,  although  it takes religious counseling and evidence of productive  zakat as an effort to improve  zakat  literacy even  better.   Keywords: Literacy of Zakat, Knowledge of Zakat basic, Dukuh Krajan Jepara